Changes in the Proliferation/Apoptosis Balance in the Bovine Ovary: A Key Early Event in Follicular Persistence - Belotti, Eduardo Matías (2017)
The objective of this work was to evaluate proliferation and apoptosis in the bovine ovary in a model of follicular persistence induced by low levels of progesterone to detect incipient changes during cystic ovarian disease development on the expected day of ovulation (day 0) and after 5, 10, and 15 days of follicular persistence. We analyzed cell proliferation by evaluating the expression of Ki-67 and apoptosis by evaluating caspase-3, BAX, and BCL2 expression. Proliferation was similar in the granulosa and theca cells of antral follicles in the P0 group (treated with progesterone up to the expected day of ovulation) and in the control group. A decrease in cell proliferation was detected after 5 days of persistence (P5) in relation to P0 (p < 0.05). Similar changes were found in the granulosa cells of the persistent follicles in relation to the control group (p < 0.05). Caspase-3 expression was similar in granulosa cells of antral follicles at early stages of persistence, with an increase after 15 days of persistence (p < 0.05). In the granulosa cells of group P10 (10 days of persistence), caspase-3 expression was reduced relative to that of antral follicles from the control group (p < 0.05). BCL2 expression was higher in granulosa cells of the persistent follicles of group P0 relative to the control follicles, with no changes in BAX expression, which was increased in persistent follicles of group P15 (p < 0.05). Similar results were observed in theca cells at initial stages of persistence. The results show that, initially, proliferation is maintained with low apoptosis and an increase in cell survival.